Learning Strategies at SMP Muhammadiyah 3 Pandaan During Covid-19 Pandemic - Muhlasin Amrullah; Devi Wulandari (Proceedings of The ICECRS, 2021)
The purpose of this study is to examine several aspects, including: the history of the establishment of SMP Muhammadiyah 3 Pandaan, learning strategies carried out in the midst of the covid 19 pandemic, learning methods, learning challenges, and effectiveness in learning at SMP Muhammadiyah 3 Pandaan. The research process uses descriptive qualitative methods. in the research process using data collection techniques by means of observation, interviews, and photos when the research was conducted. This study aims to determine the learning strategy in SMP Muhammadiyah 3 Pandaan. The strategy used at SMP Muhammadiyah 3 Pandaan in the midst of a pandemic is to use online learning strategies. Learning is carried out using zoom, google meet, wa, and youtube media, this is as an intermediary for learning in the midst of a pandemic, using these strategies can facilitate teaching and learning activities carried out by teachers and students online. SMP Muhammadiyah 3 Pandaan also experienced several challenges in carrying out learning in the midst of the covid-19 pandemic, one of which was that many students did not have the tools to do online learning such as cellphones, laptops, or computers, and some had problems such as having cellphones but many did not. have a quota or it is difficult to reach a signal when online learning is done. Although there are many challenges in carrying out learning activities in the midst of a pandemic like this, it does not eliminate the enthusiasm to keep learning even though you have to be at home online.